The effect of tualang honey cream on skin hydration and elasticity – in vivo study - Ab. Hadi, Hazrina; Syed Omar, Sharifah Shakirah (2017)
Skin moisturizers can be applied to retain skin moisture. Honey can acts as a moisturizer for the skin as it contains humectant properties. The objective of this study was to evaluate the moisturizing effects of tualang honey cream formulation on human skin. Tualang honey was developed as a cream formulation. Water was heated up to 70°C using a water bath (Fisher Scientific Model 2336, Ohio, USA). Lecithin and pectin were added and mixed well in the heated water. The mixture was then homogenized using disperser and homogenizer (El Dorado Labtech (Asia) Sdn. Bhd. Model WT-130) with a speed of 8000 RPM for 15 minutes. After being mixed well, vitamin E, glycerin, and cocobetaine were added. The oil phase which consisted of almond oil, coconut oil, jojoba oil, natural beeswax, preservative and cocobetaine were placed together and heated to 70°C. The oil phase and aqueous phase were then mixed together for 5 minutes at the same temperature of 70°C-75°C. Honey was added to the mixture and mixed well for another 5 minutes until it cooled down completely. The physical properties of the cream were then evaluated before applying the cream on 18 healthy volunteers for the duration of 4 weeks. The moisturizing effect was evaluated by measuring skin hydration and skin elasticity using DermaLab® Combo on a weekly basis. Yellowish color and smooth texture cream was prepared with pH of 4. Significant improvement in skin hydration was observed in week 2, week 3, and week 4 compared to week 1. This improvement may be contributed by the humectant property of honey. Humectants in honey act by making hydrogen bridges with water and retaining water in the stratum corneum layer. Results from the skin elasticity study indicated that there was significant reduction of retraction time (ms) recorded. As the retraction time is reduced, this indicated that the elasticity of the skin improved with the application of the tualang honey cream. In conclusion, formulated cream containing tualang honey can moisturize skin as it improves skin hydration and elasticity. Hence, tualang honey can be a promising ingredient in moisturizing creams in the future.